High performance of nitrogen and phosphorus removal in an electrolysis-integrated biofilter - Gao, Y (Water science and technology : a journal of the International Association on Water Pollution Research, 2016)
A novel electrolysis-integrated biofilter system was developed in this study to evaluate the intensified removal of nitrogen and phosphorus from contaminated water. Two laboratory-scale biofilter systems were established, one with electrolysis (E-BF) and one without electrolysis (BF) as control. The dynamics of intensified nitrogen and phosphorus removal and the changes of inflow and outflow water qualities were also evaluated. The total nitrogen (TN) removal rate was 94.4% in our newly developed E-BF, but only 74.7% in the control BF. Ammonium removal rate was up to 95% in biofilters with or without electrolysis integration with an influent ammonium concentration of 40 mg/L, and the accumulation of nitrate and nitrite was much lower in the effluent of E-BF than that of BF. Thus electrolysis plays an important role in TN removal especially the nitrate and nitrite removal. Phosphorus removal was significantly enhanced, exceeding 90% in E-BF by chemical precipitation, physical adsorption, and flocculation of phosphorus because of the in situ formation of ferric ions by the anodizing of sacrificial iron anodes. Results from this study indicate that the electrolysis integrated biofilter is a promising solution for intensified nitrogen and phosphorus removal